Sosialisasi Pelatihan Pembuatan Dimsum Dalam Meningkatkan Perekonomian Bagi Masyarakat Desa Batu Melenggang Kecamatan Hinai Kabupaten Langkat - Anjur Perkasa Alam; Asmawarna Sinaga (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2025)
The dim sum making training activity in Batu Melenggang Village, Hinai District, Langkat Regency aimed to provide new skills to the community, especially housewives, so that they could develop a home-based culinary business that could increase family income. The method used was socialization and hands-on practice, carried out by a community service team consisting of six students from the Jam'iyah Mahmudiyah Langkat Institute with 20 participants. The socialization focused on home-based food business opportunities, economic benefits, and marketing strategies, followed by practical training on dim sum making, from ingredient preparation and wrapping techniques to the steaming process. The results of the activity showed high enthusiasm among the participants, as evidenced by their active involvement in each stage and their ability to produce dim sum with good taste and appearance. The production trial resulted in 60 pieces of dim sum with a production cost of around IDR 70,000 and a potential profit of IDR 50,000–IDR 80,000 per recipe, depending on the selling price. Participants also gained an understanding of the importance of taste standards, hygiene, packaging, and simple record-keeping in running a business. The initial impact of this activity can be seen from the formation of three small business groups that immediately produce and market dim sum in the surrounding area, with average sales of 80–120 pieces per week. Thus, this training not only provides technical cooking skills but also fosters an entrepreneurial spirit and opens up opportunities for improving the family economy in the village.